2016
DOI: 10.1051/0004-6361/201628413
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the habitability of planets with Earth-like atmospheres with 1D and 3D climate modeling

Abstract: Context. The habitable zone (HZ) describes the range of orbital distances around a star where the existence of liquid water on the surface of an Earth-like planet is in principle possible. The applicability of one-dimensional (1D) climate models for the estimation of the HZ boundaries has been questioned by recent three-dimensional (3D) climate studies. While 3D studies can calculate the water vapor, ice albedo, and cloud feedback self-consistently and therefore allow for a deeper understanding and the identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 47 publications
5
29
0
Order By: Relevance
“…When assuming a relative humidity profile comparable to that of the Earth (Manabe & Wetherald 1967), this albedo leads to the global mean temperature of the Earth (288 K). Assumptions about the relative humidity and surface albedo can have a large impact on the planetary climate as shown, for example, by Godolt et al (2016). We chose a relative humidity similar to those in Kasting et al (1993b) and Kopparapu et al (2013).…”
Section: Initial Conditions and Model Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…When assuming a relative humidity profile comparable to that of the Earth (Manabe & Wetherald 1967), this albedo leads to the global mean temperature of the Earth (288 K). Assumptions about the relative humidity and surface albedo can have a large impact on the planetary climate as shown, for example, by Godolt et al (2016). We chose a relative humidity similar to those in Kasting et al (1993b) and Kopparapu et al (2013).…”
Section: Initial Conditions and Model Parametersmentioning
confidence: 99%
“…However, recent studies have shown that liquid water on a planetary surface is also possible for global mean temperatures below 273 K with temperatures as low as ∼ 235 K since, locally, the surface temperatures are above 273 K and may still allow for liquid water (e.g. Charnay et al 2013;Wolf & Toon 2013;Kunze et al 2014;Shields et al 2014;Godolt et al 2016).…”
Section: Habitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is very different for inner edge calculations, however, as differences in convective, cloud, and radiation schemes produce a wide scatter across different 1-D and 3-D models (Yang et al 2013;Kopparapu et al 2016;Kopparapu et al 2017;Bin et al 2018;Ramirez 2018a). These differences partially arise from the difficulty in simulating the water vapour feedback at higher temperatures, which is not a major concern at the HZ outer edge, where water vapour absorption is weaker (Godolt et al 2016;Ramirez and Levi 2018). Nevertheless, the trend that higher background N2 pressures push the inner edge closer to the star would likely be found in many other models as well.…”
Section: Comparison Between 1-d and 3-d Models On The Habitable Zone mentioning
confidence: 99%
“…von Paris et al 2015). As input data for the Earth-like planets orbiting G-and K-type stars in their habitable zone we use the modeled temperature and concentration profiles from Godolt et al (2016). These temperature profiles are also depicted in Fig.…”
Section: Input Datamentioning
confidence: 99%